2014
DOI: 10.3329/ptcb.v23i2.17505
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Root Culture : An Alternative Source of Bioactives in the Rare Aphrodisiac Herb Chlorophytum borivilianum Sant et Fern

Abstract: Chlorophytum borivilianum is a rare, near-endemic high value root crop. The fasciculated roots of the plant have the potential to synthesize valuable bioactives having aphrodisiac, anti stress and immuno modulatory properties. The present investigation describes an alternative protocol for the development of a stable, fast growing, non-transformed root culture system in C. borivilianum and the simultaneous quantitative analysis of total steroidal saponins, amino acids and sugars. Liquid MS fortified with vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It is easy to culture root tissues of dicot plant but in the case of monocot plants where root forms modified structures such as bulb, corm or tubers the root culture seems to be difficult but the tuberous root culture of Chlorophytum borivilianum was developed and considerable amount of saponin was quantified (Basu and Jha 2015). Effect of growth regulators was determined in the adventitious root culture of Dioscorea nipponica and it was observed that dioscin and prosapogenin C content in indole-3-butyric acid (IBA) treated roots were significantly higher as compared to 1-naphthaleneacetic acid (NAA) treated roots (Ahn et al 2005).…”
Section: Production Of Steroidal Saponin In Culture Mediamentioning
confidence: 99%
“…It is easy to culture root tissues of dicot plant but in the case of monocot plants where root forms modified structures such as bulb, corm or tubers the root culture seems to be difficult but the tuberous root culture of Chlorophytum borivilianum was developed and considerable amount of saponin was quantified (Basu and Jha 2015). Effect of growth regulators was determined in the adventitious root culture of Dioscorea nipponica and it was observed that dioscin and prosapogenin C content in indole-3-butyric acid (IBA) treated roots were significantly higher as compared to 1-naphthaleneacetic acid (NAA) treated roots (Ahn et al 2005).…”
Section: Production Of Steroidal Saponin In Culture Mediamentioning
confidence: 99%